2013
DOI: 10.1177/0734904113475858
|View full text |Cite
|
Sign up to set email alerts
|

Determination of kinetic properties of polyurethane foam decomposition for pyrolysis modelling

Abstract: A non-fire-retardant and a fire retardant polyurethane foam are tested under a nitrogen environment using thermogravimetry at different heating rates of 1, 5, 20 and 60°C min 21 to obtain the foams' decomposition behaviours. During decomposition, both foams experience two major mass loss reactions with the second reaction consuming most of the fuel. Three graphical techniques applied to calculate the kinetic properties governing each reaction are kinetic analysis, the Arrhenius plot method and the inflection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 20 publications
1
42
0
Order By: Relevance
“…Prasad et al [58] studied polyurethane foam formed out of a reaction between toluene diisocyanate (TDI)and a polyol. Pau et al [59] studied polyurethane foams made from the reaction of mainly toluene diisocyanate and polyalkoxy polyether polyol.…”
Section: Comparison Of Current Results With Published Onesmentioning
confidence: 99%
“…Prasad et al [58] studied polyurethane foam formed out of a reaction between toluene diisocyanate (TDI)and a polyol. Pau et al [59] studied polyurethane foams made from the reaction of mainly toluene diisocyanate and polyalkoxy polyether polyol.…”
Section: Comparison Of Current Results With Published Onesmentioning
confidence: 99%
“…The TG experiments have been conducted in nitrogen at four heating rates of 5, 20, 60, and 80 °C/min, with a purge flow rate of 100 mL/min. The decomposition in nitrogen may simulate the environment in flaming fires where oxygen is consumed before reaching the pyrolysis front [6]. Each MDF sample in TG experiment was subjected to two consequent runs: (1) dehydrating the sample under a peak temperature 130°C, and (2) after cooling down, linearly increasing the temperature range from 20 to 1000°C.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…For well separated sub-reactions [6] it is not hard to determine the peak temperatures, however, for materials with strong overlapped sub-reactions such as wood [4], it is always a challenge to locate these peaks. Multiple peaks and shoulders are also observed for MDF DTG curves in Fig.…”
Section: Estimation Of Pyrolysis Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyurethane foams have been widely used in buildings as constructional and furnishing materials . Previous researches have demonstrated that the decomposition of polyurethane foam in a nitrogen environment proceeds via two pyrolysis sub‐reactions described as followed.…”
Section: Introductionmentioning
confidence: 99%